Deficits Associated With Loss of STIM1 in Purkinje Neurons Including Motor Coordination Can Be Rescued by Loss of Septin 7 - Dhanya, Sreeja Kumari; Hasan, Gaiti (Frontiers in Cell and Developmental Biology, 2021)
Septins are cytoskeletal proteins that can assemble to form heteromeric filamentous complexes and regulate a range of membrane associated cellular functions. SEPT7, a member of the Septin family functions as a negative regulator of the plasma-membrane localised Store-operated Ca2+-entry (SOCE) channel, Orai in Drosophila neurons and in human neural progenitor cells. Knockdown of STIM, a Ca2+ sensor in the endoplasmic reticulum (ER) and an integral component of SOCE, leads to flight deficits in Drosophila that can be rescued by partial loss of SEPT7 in neurons. Here, we tested the effect of reducing and removing SEPT7 in mouse Purkinje neurons (PN) with loss of STIM1. Mice with complete knock-out of STIM1 in PNs exhibit several age-dependant changes. These include altered gene expression in PNs, that correlates with increased synapses between climbing fibre (CF) axons and Purkinje neuron (PN) dendrites and a reduced ability to learn a motor coordination task. Removal of either one or two copies of the SEPT7 gene in STIM1KO PNs restored expression of a subset of genes, including several in the category of neuron projection development. Importantly, rescue of gene expression in these animals is accompanied by normal CF-PN innervation and an improved ability to learn a motor coordination task in ageing mice. Thus, loss of SEPT7 in PNs, further modulates cerebellar circuit function in STIM1KO animals. Our findings are relevant in the context of identifying SEPT7 as a putative therapeutic target for various neurodegenerative diseases caused by reduced intracellular Ca2+ signaling.